2012
DOI: 10.1039/c2gc36005e
|View full text |Cite
|
Sign up to set email alerts
|

Low melting mixtures in organic synthesis – an alternative to ionic liquids?

Abstract: There is a pressing need to replace hazardous and harmful solvents with "green" or "sustainable" media. Natural compounds have recently been used to produce deep eutectic solvents, sugar melts, or ionic liquids. This review presents physicochemical data of these reaction media and highlights recent advances in their use in organic synthesis and biotransformations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
263
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(274 citation statements)
references
References 87 publications
0
263
0
1
Order By: Relevance
“…We wish to show the effect of this hydrogen-bond acceptor to the selectivity to furanic derivatives by preventing secondary reactions in the presence of different catalysts. One interesting class of solvents that was used in the conversion of carbohydrates to furanic derivatives is deep eutectic solvent (DES) [7] and low melting mixtures (LMMs) [8]. The concept of natural deep eutectic solvents was first introduced by Abbott et al in 2003 [9].…”
Section: Scheme 2 Examples Of Lmms and Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…We wish to show the effect of this hydrogen-bond acceptor to the selectivity to furanic derivatives by preventing secondary reactions in the presence of different catalysts. One interesting class of solvents that was used in the conversion of carbohydrates to furanic derivatives is deep eutectic solvent (DES) [7] and low melting mixtures (LMMs) [8]. The concept of natural deep eutectic solvents was first introduced by Abbott et al in 2003 [9].…”
Section: Scheme 2 Examples Of Lmms and Dessmentioning
confidence: 99%
“…In general, DES is formed as a result of hydrogen-bonding interactions between two components. Therefore, one of the constituents is a hydrogen-bond acceptor (usually ChCl or NH4Cl), whereas the other constituent is a hydrogen-bond donor like natural polyols (glycerol), carboxylic acids (lactic acid (Lac), oxalic acid, citric acid) or ureas [7,8,[10][11][12][13][14][15][16][17]. If carbohydrates are used as hydrogen-bond donors with ChCl, the name used is "low melting mixtures" (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that addition of agents able to break the DES complex allows recrystallization and recovery of one or both of the initial components, since these remain in their molecular state upon melting [5,6]. DES exhibit a wide range of properties which make them an attractive family of solvents for different applications in catalysis, organic synthesis, dissolution and extraction processes, electrochemistry and material chemistry [2e5, 7,8]. The [Ch]Cl:urea mixture (1:2 mol), for example, was used in the Perkin condensation of cinnamic acid [9], reduction of epoxides [10] or in an electrophilic substitution of quinone derivatives [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of several components, which associate with each other in some way and result in a considerably lower freezing point of the mixture compared with each component [9,10]. Among the variety of DES, the mixture of quaternary ammonium salt and hydrogen bond donor is the most widely used type of DES in ionothermal synthesis of molecular sieves.…”
Section: Il and Desmentioning
confidence: 99%